Large magnetic penetration depth and thermal fluctuations in a superconducting Ca 10(Pt 3As 8)[(Fe 1-xPt x) 2As 2] 5 (x=0.097) single crystal - Kim, Jeehoon (2012)
We have measured the temperature dependence of the absolute value of the magnetic penetration depth lambda(T) in a Ca10(Pt3As8)[(Fe1-xPtx)2As2]5 (x=0.097) single crystal using a low-temperature magnetic force microscope (MFM). We obtain Lambda_ab(0) aprox 1000 nm via extrapolating the data to T = 0. This large lambda and pronounced anisotropy in this system are responsible for large thermal fluctuations and the presence of a liquid vortex phase in this low-temperature superconductor with critical temperature of 11 K, consistent with the interpretation of the electrical transport data. The superconducting parameters obtained from lambada and coherence length Xi place this compound in the extreme type II regime. Meissner responses (via MFM) at different locations across the sample are similar to each other, indicating good homogeneity of the superconducting state on a sub-micron scale.